2019
DOI: 10.1007/s00125-019-4859-4
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin reduces inflammation and fibrosis biomarkers: a potential mechanism of action for beneficial effects of SGLT2 inhibitors in diabetic kidney disease

Abstract: Aims/hypothesis The sodium–glucose cotransporter 2 (SGLT2) inhibitor canagliflozin slows progression of kidney function decline in type 2 diabetes. The aim of this study was to assess the effect of the SGLT2 inhibitor canagliflozin on biomarkers for progression of diabetic kidney disease (DKD). Methods A canagliflozin mechanism of action (MoA) network model was constructed based on an in vitro transcriptomics experiment in human proximal tubular cells and molecular feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
245
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 341 publications
(251 citation statements)
references
References 33 publications
4
245
0
2
Order By: Relevance
“…Despite large-scale clinical trials showing nephroprotection promptly after initiating SGLT2i, data regarding the anti-inflammatory potential of SGLT2i in humans are rather scarce. For example, canagliflozin treatment decreased the plasma levels of biomarkers related to inflammation and fibrosis, such as tumor necrosis factor receptor 1, IL-6, matrix metalloproteinase 7 and fibronectin 1, during a two-year follow-up when analyzing samples from a clinical phase II study [42]. Dapagliflozin reduced urinary IL-6 concentrations in a post hoc analysis of a cross-over clinical trial [43].…”
Section: Discussionmentioning
confidence: 99%
“…Despite large-scale clinical trials showing nephroprotection promptly after initiating SGLT2i, data regarding the anti-inflammatory potential of SGLT2i in humans are rather scarce. For example, canagliflozin treatment decreased the plasma levels of biomarkers related to inflammation and fibrosis, such as tumor necrosis factor receptor 1, IL-6, matrix metalloproteinase 7 and fibronectin 1, during a two-year follow-up when analyzing samples from a clinical phase II study [42]. Dapagliflozin reduced urinary IL-6 concentrations in a post hoc analysis of a cross-over clinical trial [43].…”
Section: Discussionmentioning
confidence: 99%
“…An additional class of anti-diabetic medications associated with lowering inflammation are the glifozins, or SGLT2 (sodium-glucose cotransporter-2/SLC5A2) inhibitors, which attenuate reabsorption of glucose in the kidney to lower blood sugar. So far, this reported anti-inflammatory effect focuses on the kidney, cardiovascular system and pancreas, rather than lungs ( 96 , 97 ), though it has been shown to indirectly reduce pulmonary infection in diabetic mice ( 98 ). Although SGLT2 inhibitors are associated with dehydration and anorexia and therefore may pose a risk for critically ill patients, a new study focusing on hospitalized adult patients with Covid-19 commenced in April 2020, with the aim of understanding the substantial cardio- and nephroprotective effects of SLGT2 inhibitors in reducing disease progression, complications, and all-cause mortality ( 99 ).…”
Section: Type 2 Diabetes Management In Covid-19mentioning
confidence: 99%
“…The basic mechanism to explain the effects on oxidative stress may involve anti-inflammatory actions of SGLT2 inhibitors [59]. Diabetic patients treated with canagliflozin showed lower plasma levels of TNF receptor and interleukin 6 in comparison to glimepiride group [66]. Animal studies also suggested anti-inflammatory actions of SGLT2 inhibitors.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%